In Situ Programmable, Active, and Interactive Crystallization by Localized Polymerization - Kim, Kibeom; Oh, Sangmin; Suh, Bong Lim; Bae, Junghyun; Namkoong, Myeong; Kim, Yeonji; Yoon, Jinsik; Kim, Hyeli; Lim, Sujeong; Kim, In Soo; Lee, In-Gyun; Moon, Myoung-Woon; et al. (WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim, 2025)
Additive manufacturing has sought active and interactive means of creating predictable structures with diverse materials. Compared to such active manufacturing tools, current crystallization strategies remain in statistical and passive programs of crystals via macroscale thermodynamic controllers, commonly lacking active means to intervene in crystal growth in a spatiotemporal manner. Herein, a strategy toward active and interactive programming and reprogramming of crystals, realized by real-time tangible feedback on growing crystals by delicately controlling the degree of in-situ, localized photopolymerization of polymeric structures via additive manufacturing is presented. Using this strategy, crystals can be seeded, guided, and even reprogrammed in a supersaturated liquid resin. In principle, the localized formation of sparse polymeric networks within supercooled resins can induce density fluctuation to trigger seed nucleation instantaneously, whereas the formation of dense networks can lower molecules' mobilities to inhibit crystal growth. Assisted by these active triggers and deterministic procedural aspects in additive manufacturing, growing crystals can be tangibly interacted through programmed polymeric structures, strengthening deterministic characteristics in crystal growth. It is suggested that crystal growth can be programmable with deterministic hierarchies within the created crystal's morphologies within the background of inherent stochasticity in crystallization, launching an era of convolutional growth of crystals.